PENGARUH PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI KOPI KENANGAN CABANG RUKO CILANDAK KKO JAKARTA SELATAN - Erika Sintia; Wahyu Nurul Faroh (Journal of Research and Publication Innovation, 2024)
The aim of this research is to determine and test the influence of promotions and service quality on consumer purchasing decisions at Kopi Kenangan Cabang Ruko Cilandak KKO South Jakarta. This reserach used quantitative method with an associative approach. The sampling technique used was purposive random sampling which used a sample 0f 100 respondents. Data collection techniques using questionnaires and literature study. The data analysis techniques used are instruments testing, classical assumption testing, linear regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The results of the partial hypothesis test between promotion and purchasing decisions obtained a tcount value 8,813 > 1,660 with a significant level of 0,000 < 0,05. Then H0 is rejected and Ha is accepted. The results of the partial hypothesis test between service quality and purchasing decisions obtained a tcount value 1,998 > 1,660 with a significant level of 0,049 < 0,05. Then H0 is rejected and Ha is accepted. The results of the simultaneous hypothesis test between promotion, service quality and purchasing decisions obtained a Fcount value 178,090 > Ftable 3,09 with a significant level of 0,000 < 0,05. Then H0 is rejected and Ha is accepted. The results of the coefficient of determination of promotion and service quality simultaneously contributed to the purchasing decisions variable 78,6% while the remaining 21,4% was caused by other variables.